Clinical Microbiological Aspects of Epileptic Seizures in the Tropical Countries with Specific Focus on Nigeria - Ijeoma Kanu; Ebere C. Anyanwu; Nkechi C. Nwachukwu; John E. Ehiri; Joav Merrick (The Scientific World Journal)
Epilepsy is a common neurological disorder; however, in Nigeria and other tropical regions, the causes of epileptic seizures differ greatly in etiology. This paper is an attempt to highlight some possible microbiological aspects of epileptic seizures. A literature review was carried out to identify the extent to which microbial infections were involved in the elicitation of epileptic seizures. Data were collected from several clinics in the community and hospitals in Nigeria and correlated with the evidence from the literature review. It was found that different microbial agents including viral, bacterial, protozoa, and fungal agents were involved in several aspects of epileptic seizures. Malaria was found to cause more than 88% of childhood epileptic seizures and 12% of adult seizures. Generalized tonic-clonic seizures occurred in more than 40% of adult patients. Partial seizures were uncommon. Cases of epileptic seizures associated with bacteria (e.g., brucellosis), viral, fungal, and protozoa infections were frequently reported. Malaria, tapeworm, and cysticercosis were some of the common infectious causes of epilepsy; however, in some cases, the cause remained unknown. From these findings, it was evident that microbiological aspects of epilepsies are possible research areas that might be developed. It is believed that the unraveling of the various microbiological factors in epileptic seizures would have important implications for understanding the underlying neurobiology, evaluating treatment strategies, and perhaps planning health-care resources for the affected. It will also help to improve the prognostic factors in initial seizure symptomatic etiology and presence of any structural cerebral abnormalities.